1995
DOI: 10.1037/0022-3514.69.5.903
|View full text |Cite
|
Sign up to set email alerts
|

Racial identity, academic achievement, and the psychological well-being of economically disadvantaged adolescents.

Abstract: The relation between racial identity and personal psychological functioning was examined within the framework of the "racelessness" construct proposed by Fordham and Ogbu (S. Fordham, 1988; S. Fordham & J. U. Ogbu, 1986). These researchers have proposed that academically successful African American students achieve their success by adopting behaviors and attitudes that distance them from their culture of origin, resulting in increased feelings of depression, anxiety, and identity confusion. Studies 1 and 2 des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 52 publications
7
164
1
Order By: Relevance
“…Obviously, resistance to schooling is not limited to minority students. Rather, there are inherent constraints in all forms of schooling, such as its compulsory and public nature, that evoke resistance in some students regardless of their social and cultural backgrounds (Arroyo and Ziegler, 1995). Still, minority children may experience more difficulty in engaging with their schoolwork, when behavioral norms and repertoires in class differ greatly from familiar norms and practices at home.…”
Section: Cultural Difference: Discontinuity Between Family and Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, resistance to schooling is not limited to minority students. Rather, there are inherent constraints in all forms of schooling, such as its compulsory and public nature, that evoke resistance in some students regardless of their social and cultural backgrounds (Arroyo and Ziegler, 1995). Still, minority children may experience more difficulty in engaging with their schoolwork, when behavioral norms and repertoires in class differ greatly from familiar norms and practices at home.…”
Section: Cultural Difference: Discontinuity Between Family and Schoolmentioning
confidence: 99%
“…Even in the case of more aspiring ethnic minority families, negative peer pressure or low teacher expectations may result in situationally induced disengagement with learning (D'Amato, 1993). Resistance to schooling in disadvantaged minority youth has been associated with three types of explanatory factors: (a) poor school adjustment (Okagaki et al, 1996), (b) identity conflict (Arroyo and Ziegler, 1995), and (c) stereotype threat (Steele, 1997).…”
Section: Perceived Opportunities: the Attitude-achievement Paradoxmentioning
confidence: 99%
“…For example, Arroyo and Zigler (1995) found that all high achieving students, whether African or European American, have a hard time balancing peer acceptance with academic achievement. Furthermore, using the National Educational Longitudinal Survey (NELS), Cook and Ludwig (1998) found that Black and White students perform roughly the same in high school net of family background (measured as mother's education, family income, and whether the student had an absent father).…”
Section: Geneticsmentioning
confidence: 99%
“…Rejection of Anti-Effort Norms: Students rated their rejection of anti-effort norms on a 3-item 5-point scale (1= strongly disagree, 5= strongly agree, Arroyo & Zigler, 1995), e.g., "I act less intelligent than I am so other students won't make fun of me" (reverse coded) Higher scores represent rejection of anti-effort norms (M = 4.29, SD = .84, α = .84). The two emotional engagement with school scales were correlated (r = .25, p < .01), though not enough to warrant averaging the two scales to create a composite.…”
Section: Emotional Engagement With Schoolmentioning
confidence: 99%